Strategic Monitoring and Evaluation Practices in Local Government Performance Accountability Systems - Tiara Anvadilla (Jurnal Studi Multidisiplin Ilmu, 2026)
Purpose: This study examines how monitoring and evaluation practices function within the strategic management cycle of a public organization at the local government level, using the Belitang area of East Ogan Komering Ulu Regency, Indonesia, as the empirical setting. The paper investigates how monitoring and evaluation are implemented, what constraints limit their effectiveness, and how performance accountability can be strengthened.Research Methodology: A qualitative case study design was used, drawing on document analysis of regional planning and performance reports, semi-structured interviews with regional apparatus officials, and thematic analysis guided by an evidencebased performance management framework.Results: The findings show that monitoring and evaluation in the study area remain largely administrative rather than substantive. Four interrelated constraints were identified: limited human resource capacity for analysis, fragmented information systems, a weak organizational evaluation culture, and insufficient follow-up on evaluation findings.Conclusions: Monitoring and evaluation are essential components of strategic management in public organizations, yet their contribution to performance improvement depends on integration with planning, information systems, and organizational learning routines rather than compliance reporting alone.Limitations: The single-site qualitative design limits statistical generalizability, and reliance on retrospective interview accounts introduces potential recall bias.Contributions: The study extends performance management literature by illustrating how national accountability frameworks translate into practice at the sub-district level and offers a practical model for strengthening evaluation utilization in resource-constrained local governments.